Urbanizarse o migrar: ¿Cuáles opciones frente la crisis? El devenir de las comunidades cafetaleras en el centro de Veracruz, México - Hoffmann, Odile (1994)
The sharp drop in the price of coffee since 1989 took small farmers by surprise at the time when they must adapt to the new rules of productions and marketing under the modernizing polices of the Salinas de Gortari government (1988-1994). Migrations are one response to the crisis (or crises). While seemingly an individual one, they affect the social, political and cultural future of those communities. This study discusses the emerging migratory processes in central Veracruz, and suggests that while some communities may attain a degree of “retrofitting” thanks to nearby urban centers offering job opportunities, others are undergoing long-distance, collective migratory processes which threaten the very reproduction of the rural community per se.